Star wars US tools of space supremacy - Wirbel, Loring (Pluto Press, 2004)
The expansion of space militarization forms a common thread with the explicit unilateral empire-building of the Bush administration. But just as Star Wars did not begin with the Missile Defense Agency, preventive war theory did not originate with Donald Rumsfeld. Advocates of military space always were on the front line of those demanding global dominance. Loring Wirbel argues that the seeds for the current space supremacy doctrine were sown at the end of the Cold War, in the early days of the Clinton administration. Examining the evolution of space-based tools, Wirbel shows that missile defense strategy is part of a dangerous US move to wage endless preventive war and demand global supremacy over allies and adversaries alike.Star Wars: US Tools of Space Supremacy provides a fresh look at the role of space as an enabler of the Bush administration's plans for endless preventive war. It debunks the benign notions of missile defence, and expands the definition of space supremacy beyond that of weapons in space, to include the unilateral misuse of space-based intelligence, communications, and targeting technologies.